Law Enforcement Against the Sale of Alcoholic Beverages in Gorontalo City - Laode, Chyntiya Permatasari; Darmawati, Darmawati; B, Sumiyati (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Alcoholic beverages are basically a form of disruption to the lives and livelihoods of the community, therefore, philosophically, in supervising and regulating the sale of alcoholic beverages circulating in the Gorontalo City area, the Gorontalo City Government has formed regulations that can provide comfort and order for the community. This study uses the empirical research method (field research) or field research, namely research whose objects are regarding symptoms, events, and phenomena that occur in society, institutions or countries that are non-library by looking at. With Research Results In an effort to overcome the circulation of alcoholic beverages, the Police will make 3 (three) efforts, namely: preventive efforts, preventive efforts and repressive efforts